Elaboración de una guía metodológica para el diseño e implementación de Home Studios en el ámbito local - Vásquez Peñafiel, Diego Alberto (2011)
Since the invention of sound recording, artists have found an accelerated development of technologies dedicated to provide the best sound quality. Decades ago, for instance, the only way to have a high-end recording was to spend a large sum of money in booking a professional recording studio. Low-priced recording at that time was impossible because equipment was overly expensive, and there were no cheaper options whatsoever. Nowadays, with the help of the development of digital audio and convenient prices on faster computers, users can make excellent recordings with a small investment. Nevertheless, a lack of knowledge is causing users not to reach the maximum potential of available resources. The objective of this guide is to help individuals (regardless of his or her prior knowledge) that have the desire to set-up a place to record audio. With this reason in mind, a survey took place in order to find out the areas that potential readers felt unaware with having their personal studio. Once the users shared their preferences and topics of interest, the investigator began developing a research study with both, a wide variety of literature and by consulting specialists that helped with helpful tools and input. In addition, a recording studio was designed and conditioned using all the concepts and suggestions obtained with this research; and finally, this following document was prepared to cover all the essential information to meet its proposed objectives.